Salts of amino acids with hexafluorosilicate anion - Ghazaryan, V.V.; Fleck, M.; Petrosyan, A.M. (Journal of crystal growth, 2013)
In this work we present our preliminary results on the systematic search for salts of amino acids with hexafluorosilicate (SiF62−) anion. Three types of simple salts have been obtained: 2A+·SiF62− (2Gly+·SiF62−, 2l-Phe+·SiF62−, 2l-Val+·SiF62−, 2l-Glu+·SiF62−, 2l-His+·SiF62−), A2+·SiF62− (l-His2+·SiF62−, l-Lys2+·SiF62−, l-Orn2+·SiF62−) and 2(A···A+)·SiF62− (2(Bet···Bet+)·SiF62−). Furthermore, one example of mixed salts with different anions, including SiF62−, viz. 2l-His2+·2BF4−·SiF62−·2H2O is presented. It was found that the salts of amino acids with SiF62− anion tend to form crystal hydrates and the SiF62− anion is often disordered within the structures. ► First report on a new class of amino acids salts with hexafluorosilicate anion. ► Crystals of three types of simple salts are reported. ► An example of mixed salts with different anions is presented.